Tocilizumab versus anakinra in COVID-19: results from propensity score matching - Arcani, Robin; Correard, Florian; Suchon, Pierre; Kaplanski, Gilles; Jean, Rodolphe; Cauchois, Raphael; Leprince, Marine; Arcani, Vincent; Seguier, Julie; De Sainte Marie, Benjamin; Andre, Baptiste; Koubi, Marie; et al. (Frontiers in Immunology, 2023)
Background Tocilizumab and anakinra are anti-interleukin drugs to treat severe coronavirus disease 2019 (COVID-19) refractory to corticosteroids. However, no studies compared the efficacy of tocilizumab versus anakinra to guide the choice of the therapy in clinical practice. We aimed to compare the outcomes of COVID-19 patients treated with tocilizumab or anakinra. Methods Our retrospective study was conducted in three French university hospitals between February 2021 and February 2022 and included all the consecutive hospitalized patients with a laboratory-confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection assessed by RT-PCR who were treated with tocilizumab or anakinra. A propensity score matching was performed to minimize confounding effects due to the non-random allocation. Results Among 235 patients (mean age, 72 years; 60.9% of male patients), the 28-day mortality (29.4% vs. 31.2%, p = 0.76), the in-hospital mortality (31.7% vs. 33.0%, p = 0.83), the high-flow oxygen requirement (17.5% vs. 18.3%, p = 0.86), the intensive care unit admission rate (30.8% vs. 22.2%, p = 0.30), and the mechanical ventilation rate (15.4% vs. 11.1%, p = 0.50) were similar in patients receiving tocilizumab and those receiving anakinra. After propensity score matching, the 28-day mortality (29.1% vs. 30.4%, p = 1) and the rate of high-flow oxygen requirement (10.1% vs. 21.5%, p = 0.081) did not differ between patients receiving tocilizumab or anakinra. Secondary infection rates were similar between the tocilizumab and anakinra groups (6.3% vs. 9.2%, p = 0.44). Conclusion Our study showed comparable efficacy and safety profiles of tocilizumab and anakinra to treat severe COVID-19.